Demand and supply changes in the livestock sector and their impact on smallholders: The case of dairying in Kenya - Staal, Steven J.; Waithaka, M.M.; Owour, G. A.; Herrero, Mario (Nottingham University Press, 2004)
This summary Report presents recent demand and supply trends in the dairy sector of Kenya in the 1990s, to highlight the consequences of liberalization and macroeconomic factors. Sections discuss: the evolution of policies in the dairy sector in Kenya; supply factors in the dairy sector (production factors, returns to dairy production, milk marketing, and policies); and the demand factors. It is indicated that policies in the 1990s made it more difficult for smallholder farmers to access some services. However, the milk market environment improved due to open competition and smallholder production was profitable across different settings. It is also indicated that a high level of milk consumption continues, but demand may be adversely affected by the low rate of income growth.